EFEK PARAMETER QUALITY PADA KOMPRESI JPEG TERHADAP KUALITAS CITRA DIGITAL DAN RASIO KOMPRESI - helmie Arif Wibawa; Aris Sugiharto (Jurnal Masyarakat Informatika)
In general, digital image have large amount of file size so that inefficient if wanted to save or transmit it to another place. We require a method to reduce the file. The method which used many is  compression. One of them is JPEG compression. At this compression, there is a parameter used to know the quality of compression called quality parameter. So that necessary to check quality parameter effect on JPEG compression to digital images and compression ratio.